2020
DOI: 10.3390/f11080882
|View full text |Cite
|
Sign up to set email alerts
|

Litter Decomposition and Nutrient Dynamics in Fire-Affected Larch Forests in the Russian Far East

Abstract: Russian boreal forests hold a considerable carbon (C) stock and are subjected to frequent surface fires that unbalance C storage and ecosystem function. Although postfire ecological changes aboveground are well understood, biological C flows (e.g., decomposition in the postfire period) remain unclear. We present the results of a long-term field litterbag experiment on needle litter decomposition in typical Larix gmelinii boreal forests in the Russian Far East. For 3 years, we measured mass loss, C and nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
1
0
1
Order By: Relevance
“…Inconsistent with other study area, the litter decomposition mainly concentrates on May to September in our study area when the litter decomposition rate is higher, while it is stagnant in winter. The litter decomposed at the study period, losing more than 23% of the initial mass (Figure 3), which is close to previous study in temperate region [37,38]. The rapid mass loss and leaching at this study period may have significant effects on soil N dynamics.…”
Section: Impact Of Litter Manipulations On Soil N Availabilitysupporting
confidence: 86%
“…Inconsistent with other study area, the litter decomposition mainly concentrates on May to September in our study area when the litter decomposition rate is higher, while it is stagnant in winter. The litter decomposed at the study period, losing more than 23% of the initial mass (Figure 3), which is close to previous study in temperate region [37,38]. The rapid mass loss and leaching at this study period may have significant effects on soil N dynamics.…”
Section: Impact Of Litter Manipulations On Soil N Availabilitysupporting
confidence: 86%
“…Our results showed that the k value did not continue to accelerate after disturbance by fire (Figure 3, Tables 2 and A1). This result was different from the initial increase of k value [30][31][32] and the decrease after fire disturbance [1,[49][50][51][52] as well as the research results that there is no change in the early stage 15 years after fire disturbance, and it was suppressed in the later stage [53] (Table A2). For boreal forest ecosystems, sunlight and rain become important regulatory factors in the upper litter layer in the short term after fire disturbance [54].…”
Section: Effect Of Fire Disturbance On Kcontrasting
confidence: 64%